مستوى مراعاة الوالدين لأساليب التربية الإسلامية وعلاقته بمستوى الإنتماء للأسرة لدى طلبة الجامعات الأردنية - خطاطبة، عدنان مصطفى إبراهيم; التميمي، أحمد خالد (جامعة الكويت - مجلس النشر العلمي, 2015)
هدفت الدراسة الحالية إلى معرفة مستوى مراعاة الوالدين لأساليب التربية الإسلامية، وعلاقته بمستوى الانتماء للأسرة لدى طلبة الجامعات الأردنية من منظور التربية الإسلامية، ولتحقيق هدف الدراسة، قام الباحثان بتصميم أربعة مقاييس: مقياس مستوى مراعاة الأم لأساليب التربية الإسلامية، ومقياس مستوى مراعاة الأب لأساليب التربية الإسلامية، ومقياس مستوى الانتماء للأسرة، ومقياس البيئة الأسرية). تم استخدام المنهج الكمي بأسلوب وصفي، كما تم استخدام المنهج الكمي العلائقي (تحليل المسار) لمعرفة القدرة التفسيرية لكل من المتغيرات المتنبئة: (أساليب الأب، أساليب الأم، البيئة الأسرية) على تفسير المتغير المتنبأ به: (الانتماء للأسرة). وبلغ عدد المشاركين في الدراسة (761) طالباً وطالبة، من طلبة البكالوريوس في الجامعتين: الأردنية واليرموك، وتوصلت الدراسة إلى نتائج أهمها: أولاً -أن مستوى مراعاة كل من الأمهات والآباء لأساليب التربية الإسلامية كان كبيراً على المقياس الكلي، وعلى المجالات الفرعية جميعها. ثانياً -أن مستوى توافر الظروف التربوية الإسلامية في البيئة الأسرية، كان (كبيراً). ثالثاً- أن مستوى انتماء طلبة الجامعات الأردنية لأسرهم كان (كبيراً) على المقياس الكلي، وعلى المجالات الفرعية جميعها. رابعاً -وجود علاقة سببية مباشرة بين كل من: (مستوى مراعاة الأم لأساليب التربية الإسلامية، ومستوى مراعاة الأب لأساليب التربية الإسلامية) من جهة، والبيئة الأسرية من جهة أخرى، ووجود علاقة سببية مباشرة وغير مباشرة بين كل من: (مستوى مراعاة الأم لأساليب التربية الإسلامية، ومستوى مراعاة الأب لأساليب التربية الإسلامية) من جهة، وبين الانتماء من جهة أخرى، ووجود علاقة سببية مباشرة بين البيئة الأسرية والانتماء.
The purpose of this study is to determine the degree of the parental consideration of the Islamic Education approaches and its relationship to the familial belonging degree from the Islamic Education perspective. In order to achieve the objectives of the study, the researcher designed four measuring instruments: The first is the scale of the degree of father’s consideration of the Islamic Education approaches, the second is the scale of the mother’s considera¬tion of the Islamic Education approaches, the third is the scale of degree of the familial belonging and the fourth is the scale of the family environment. The quantitative method was used descriptively. The relational method was also used (path analysis) to investigate the interpretive ability for the predictor variables: (father’s approaches, the mother’s approaches, and the family environ¬ment) on interpreting the predicted variable: (belonging to the family). The participants of the study were 761 undergraduate students (males and females) from the University of Jordan and Yarmouk University. The study arrived at results, most important of which are the following: 1. The degree of the father’s and mother’s consideration of the Islamic education approaches was high on the overall scale and on all the sub domains. 2. The degree of the availability of the Islamic Education in the family environment was high. 3. The degree of the Jordanian university student’s familial belonging was high on the overall scale and all sub domains. 4. There was a direct causal relationship among the father’s and mother’s consideration of the Islamic Education approaches and the familial environment and there was a direct and indirect causal relationship among the father’s and the mother’s degree of the consideration of Islamic Education approaches and familial belonging. There was also a direct causal relationship between the family environment and familial belonging.
Keywords: الأباء و الأمهات -- التربية الإسلامية -- الإنتماء -- الأسرة -- طلاب الجامعات ، الأردن